Tradisi Pantang Larang di Masyarakat Melayu Indragiri Hilir: Tinjauan Semiotika Roland Barthes - Indiani, Denisa; Andriyani, Noni (UIR Press, 2024)
This study aims to describe, analyze, interpret, and conclude taboo prohibitions and semiotic codes in the Community of Pekan Arba Sub-District of Tembilahan, Indragiri Hilir Regency. Through a descriptive method, data were collected through observation, interviews, and recordings, then analyzed in detail. The results of the analysis of hermeneutic and semiotic codes indicate that the use of these codes plays a crucial role in constructing puzzles, generating tension, and conveying deep and complex meanings. Codes such as suggestion, disruption, and partial answers effectively stimulate interpretation and reflection on the implicit messages in the taboos. Furthermore, symbolic, narrative action, and cultural codes also provide insights into the culture, beliefs, and norms of the community. Thus, taboos are not just rules but also a medium for conveying relevant social, educational, spiritual, and traditional values to society.